Banking and monetary statistics - Board of Governors of the Federal Reserve System (U.S.) (Washington, D.C. : Board of Governors of the Federal Reserve System, 1943)
General statistics of all banks in the US and the history of banking functions by a variety of institutions.
"The statistics in most cases cover the period since 1914, when the Federal Reserve System was established."--Pref.
Includes bibliographical footnotes and index.
sju 22/01/2019
Loans
Keywords: Banks and banking; Money